2005
DOI: 10.1111/j.1559-1816.2005.tb02176.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Victims' Social Support on Attributions of Blame in Female and Male Rape

Abstract: One hundred and twenty-one participants read a report of an incident of rape and evaluated the victim and the perpetrator. Two ANOVAs showed that social support and participant gender influenced blame attributed to the victim, while victim gender influenced blame attributed to the perpetrator. Socially supported victims were blamed less than unsupported victims. Men were more blaming of rape victims than women, but further analyses showed this was mediated by attitudes towards gender roles. Men held significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 61 publications
(53 reference statements)
3
44
3
3
Order By: Relevance
“…Surprisingly, similar results are found for adolescent victims, who "are treated as quasi adults despite being under the legal age of consent" (Davies et al, 2009, p. 335). This could either be due to observers finding male rape difficult to understand and accept, or due to observers perceiving the male victim to be unmasculine and submissive (Anderson & Lyons, 2005). Although less convincing and widespread, contradictory results have also been reported, whereby women are blamed to a greater extent for their victimization than men (Idisis, Ben-David, & Ben-Nachum, 2007;Schneider, Soh-Chiew Ee, & Aronson, 1994), leading some researchers to propose that there are additional moderating variables at work when rape blame attributions are being formulated (Mitchell, Angelone, Kohlberger, & Hirschman, 2009).…”
Section: Victim Gendermentioning
confidence: 89%
See 3 more Smart Citations
“…Surprisingly, similar results are found for adolescent victims, who "are treated as quasi adults despite being under the legal age of consent" (Davies et al, 2009, p. 335). This could either be due to observers finding male rape difficult to understand and accept, or due to observers perceiving the male victim to be unmasculine and submissive (Anderson & Lyons, 2005). Although less convincing and widespread, contradictory results have also been reported, whereby women are blamed to a greater extent for their victimization than men (Idisis, Ben-David, & Ben-Nachum, 2007;Schneider, Soh-Chiew Ee, & Aronson, 1994), leading some researchers to propose that there are additional moderating variables at work when rape blame attributions are being formulated (Mitchell, Angelone, Kohlberger, & Hirschman, 2009).…”
Section: Victim Gendermentioning
confidence: 89%
“…These studies have found that male observers generally hold more stereotypical beliefs towards gender roles than female observers, which, in turn, leads to the formation of causal attributions about rape incidents and harsher attitudes towards victims and a greater degree of victim blame (Anderson & Lyons, 2005;Grubb & Turner, 2012). Studies also suggest gender role attitudes to have a mediating effect between observer ethnicity and degree of blame, and could, therefore, account for cross-cultural differences in rape victim blaming (Yamawaki & Tschanz, 2005).…”
Section: Gender Role Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, a large number of studies suggests that men are more likely to engage in victim blaming (e.g., Anderson & Lyons, 2005;Bendixen, Henriksen, & Nøstdahl, 2014;Black & Gold, 2008;Durán, Moya, Megías, & Viki, 2010;Ferrão, Gonçalves, Giger, & Parreira, in press;Gölge et al, 2003;Grubb & Harrower, 2009;Harrison, Howerton, Secarea, & Nguyen, 2008;Mitchell, Angelone, Kohlberger, & Hirschman, 2009;Paul, Kehn, Gray, & Salapska-Gelleri, 2014;Schneider, Mori, Lambert, & Wong, 2009;Strömwall, Landström, & Alfredsson, 2014;Yamawaki & Tschanz, 2005). …”
Section: An Overview Of Rape Victim Blaming Observer Gendermentioning
confidence: 99%